The Clinical Significance and Mechanisms of REG4 in Human Cancers - Zhang, Junyan; Zhu, Zhi; Miao, Zhifeng; Huang, Xuanzhang; Sun, Zhe; Xu, Huimian; Wang, Zhenning (Frontiers in Oncology, 2021)
Regenerating islet-derived type 4 (REG4), belonging to the calcium-dependent lectin gene superfamily, has been reported to be abnormally expressed in various cancers, such as colorectal, gastric, gallbladder, pancreatic, ovarian, prostate and lung cancer. REG4 is associated with relatively unfavorable prognosis and clinicopathologic features in cancers such as advanced tumor and nodal stage, histological differentiation, liver and peritoneal metastasis. Moreover, REG4-positive cancer cells showed more frequently resistance to chemoradiotherapy, especially 5-FU-based chemotherapy. REG4 participates in many aspects of carcinogenesis including cell proliferation, apoptosis, cell cycle, invasion, metastasis and drug resistance. The mechanisms underlying are complex and involve a series of signaling mediators and multiple pathways. REG4 may be a potential diagnostic and prognostic biomarker as well as a candidate therapeutic target in cancer patients. In this review, we systematically summarize the advance about the clinical significance, biological functions as well as mechanisms underlying of REG4 in cancer to provide new direction for future cancer research.